Adult height in relation to the risk of colorectal cancer among the Japanese population: an evaluation based on systematic review and meta-analysis. (29th December 2021) - Shrestha, Rachana Manandhar; Mizoue, Tetsuya; Sawada, Norie; Matsuo, Keitaro; Wada, Keiko; Tanaka, Keitaro; Lin, Yingsong; Sugawara, Yumi; Takimoto, Hidemi; Kimura, Takashi; Ito, Hidemi; Kitamura, Tetsuhisa; et al.
Abstract: Objective: The association between adult-attained height and risk of colorectal cancer remains elusive among the Japanese population. We performed a systematic review and meta-analysis of epidemiological studies in Japan. Methods: We systematically searched the MEDLINE (PubMed) and Ichushi databases and complemented it with manual search to identify eligible studies. We extracted relative risks or odds ratios from the selected studies and conducted meta-analysis to estimate the summary relative risk with 95% confidence interval. We made the final judgment based on a consensus of the research group members considering both epidemiological evidence and biological plausibility. Results: This systematic review identified four cohort and one case–control studies among the Japanese. The meta-analysis of these five studies showed the summary relative risk of 1.21 (95% confidence interval: 1.07–1.35) of overall colorectal cancer for the highest vs. lowest categories of height. In the analysis by the cancer subsite, the association was significant for colon cancer with a summary relative risk of 1.26 (95% confidence interval: 1.10–1.45) but not for rectal cancer 1.05 (95% confidence interval: 0.71–1.54). In the analysis by sex, tall stature was associated with a significantly increased risk of overall colorectal cancer in both sexes; the summary relative risk was 1.21 (95% confidence interval: 1.04–1.41) in men and 1.20 (95% confidence interval: 1.00–1.44) in women, respectively. Conclusions: The evidence to support that adult-attained height is associated with increased risk of colorectal cancer (colon cancer) among the Japanese population is 'probable'. Abstract : The present study concluded that there is 'probable' evidence to support that adult-attained height is associated with increased risk of colon cancer among Japanese population.